Effect of bone marrow mesenchymal stem cell transplantation combined with lugua polypeptide injection on osteoarthritis in rabbit knee joint. (4th July 2022) - Huang, Huajun; Zhang, Ping; Xiang, Chunling; Zeng, Canjun; Du, Qingjun; Huang, Wenhua
ABSTRACT: Purpose: This study aimed to elucidate the effect of bone marrow mesenchymal stem cell (BMSC) transplantation combined with the administration of Lugua polypeptide injection into the knee joint cavity to treat knee osteoarthritis (KOA) in rabbits. Material and methods: Sixty white New Zealand rabbits were randomly divided into the blank, model, Lugua polypeptide, BMSC, and combined (Lugua polypeptide plus BMSC) groups, with 12 rabbits in each group. The mRNA and protein expression levels of cyclin D1, bcl-2, TIMP-1, p21, caspase-3, Bax, MMP-1, MMP-13, TLR-4, and NF-κB p65 in chondrocytes, and levels of IL-1, NO, TNF-α, and IL-6 in the synovial fluid were compared. Results: The severity of cartilage damage in the combined group was significantly less ( P <0.01). Compared to the MG, the mRNA and protein expression levels of cyclin D1, bcl-2 and TIMP-1 in chondrocytes of the three other groups were significantly increased, while those of p21, caspase-3, Bax, MMP-1, MMP-13, TLR-4, and NF-κB p65 in the chondrocytes and levels of IL-1, NO, TNF-α, and IL-6 in the synovial fluid of the three other groups were significantly reduced ( P <0.05). The aforementioned indicators in the combined group were significantly better than those of the Lugua polypeptide and BMSCs groups ( P <0.05). Conclusions: BMSC transplantation combined with Lugua polypeptide injection may improve KOA-related cartilage tissue damage in rabbits.